PENERAPAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DALAM MANAJEMEN SUMBER DAYA MANUSIA PADA PERGURUAN TINGGI - Dadang Sudirno (MAKSI, 2014)
Organizational Citizenship Behavior (OCB) is the attitude or behavior of anemployee who knowingly and voluntarily for extra work beyond the job description has. Thereare three aspects relating to the creation of OCB that is moral, commitment, and motivationof employees. The results of previous studies stating that the OCB will inevitably impact thequality of service therefore OCB can be used as one method of approach in human resourcemanagement to improve employee performance. This method can be applied to measure theperformances of lecturers at the university. The university leaders must be able to create asystem in order to create a positive OCB for academicians who are thus able to provide themaximum benefit for the existing academic community.Key wods: Organizational citizenship behavior, moral, comitment,motivation.